Blood pressure and burden of hypertension in Cameroon, a microcosm of Africa: a systematic review and meta-analysis of population-based studies. Issue 11 (November 2019) - Kuate Defo, Barthelemy; Mbanya, Jean Claude; Kingue, Samuel; Tardif, Jean-Claude; Choukem, Simeon Pierre; Perreault, Sylvie; Fournier, Pierre; Ekundayo, Olugbemiga; Potvin, Louise; D'Antono, Bianca; Emami, Elham; Cote, Robert; et al.
Abstract : Objective: To estimate national and geography-based variations in blood pressure and burden of hypertension in Cameroon, generally called 'miniature Africa'. Methods: PubMed, Medline, EMBASE, CINHAL, Web of Science, Popline, Scopus and BDSP were searched through November 2018, for hypertension studies among Cameroonians aged at least 18 years. Hypertension was measured as SBP at least 140 mmHg or DBP at least 90 mmHg. Random-effects meta-analysis was used. Results: Twenty studies involving 46 491 participants met inclusion criteria. Overall hypertension prevalence was 30.9% [95% confidence interval (CI) 27.0–34.8]: 29.6% (24.1–35.1) and 32.1% (27.2–37.1) in 1994–2010 and 2011–2018, respectively. Of hypertensive participants, only 24.4% (18.9–30.0) – 31.6% (21.0–42.3) and 20.8% (14.0–27.7) in 1994–2010 and 2011–2018, respectively – were aware of their status, 15.1% (10.6–19.6) were taking antihypertensive medications and 8.8% (5.7–11.9) – 10.4% (7.5–13.3) and 8.3% (4.4–12.3) in 1994–2010 and 2011–2018, respectively – were controlled. Hypertension prevalence varied by sex: 34.3% (30.0–38.6) for men and 31.3% (26.5–36.1) for women; ethnicity: from 3.3% (0.4–6.2) among Pygmies to 56.6% (49.4–63.8) among Bamileke; urbanity: 25.4% (17.1–33.7) for rural and 31.4% (27.3–35.5) for urban dwellers; agroecological zone: from 35.1% (28.9–41.3) in Tropical highlands to 28% (20.1–35.9) in Guinea-Savannah; and subnational region: from 36.3% (27.8–44.9) in the West to 17.1% (9.9–44.2) in the South. Conclusion: Cameroon's hypertension prevalence is high and increasing whereas awareness, treatment and control are low and declining. Emerging patterns call urgently for effective campaigns to raise hypertension awareness alongside strategies for hypertension prevention and BP control. Abstract : Supplemental Digital Content is available in the text